If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6x + -9) = 0 Reorder the terms: 2(-9 + 6x) = 0 (-9 * 2 + 6x * 2) = 0 (-18 + 12x) = 0 Solving -18 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 12x = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 12x = 0 + 18 12x = 0 + 18 Combine like terms: 0 + 18 = 18 12x = 18 Divide each side by '12'. x = 1.5 Simplifying x = 1.5
| 420=x(x-1) | | -4/3x-4=1/6x-7/2 | | -8f=184 | | 20b-4b-2b*10= | | 5x=12.5(3.83) | | 53*n=22684 | | -10/12x=6/12 | | p^2+13p+10= | | 3+-1=-7-9 | | 16x^2-100= | | 12x+19=5x+19 | | M=7006-2237 | | 3=4-1/5w | | 100-16x^2= | | 254*56=y | | 28x^2+7x+8= | | 7p-2(p-5)=-5 | | 7x+7y=74 | | 69=-n+4(8n-6) | | a/3-7=-10 | | 10x-2=2x^2+6x | | 6342+8261=x | | 7x+7y=77 | | 18/3=2xs | | 4/5-2p/5=6/4 | | -3+-8=-2+4 | | 9a=25 | | 4x-2/8-4x=10 | | 3a-3a-3-0.33*a= | | 9.75=4.75x+1.25 | | 10(10+18)=x(x+3) | | 10v-v=27 |